Interactions of cantharidin-like inhibitors with human protein phosphatase-5 in a Mg2+ system: molecular dynamics and quantum calculations - Assis, Letícia C; de Castro, Alexandre A; Prandi, Ingrid G; Mancini, Daiana T; de Giacoppo, Juliana O S; Savedra, Ranylson M L; de Assis, Tamiris M; Carregal, Juliano B; da Cunha, Elaine F F; Ramalho, Teodorico Castro (Journal of molecular modeling, 2018)
The serine/threonine protein phosphatase type 5 (PP5) is a promising target for designing new antitumor drugs. This enzyme is a member of the PPP phosphatases gene family, which catalyzes a dephosphorylation reaction: a regulatory process in the signal transduction pathway that controls various biological processes. The aim of this work is to study and compare the inhibition of PP5 by ten cantharidin-like inhibitors in order to bring about contributions relevant to the better comprehension of their inhibitory activity. In this theoretical investigation, we used molecular dynamics techniques to understand the role of key interactions that occur in the protein active site; QM calculations were employed to study the interaction mode of these inhibitors in the enzyme. In addition, atoms in molecules (AIM) calculations were carried out to characterize the chemical bonds among the atoms involved and investigate the orbital interactions with their respective energy values. The obtained results suggest that the Arg275, Asn303, His304, His352, Arg400, His427, Glu428, Val429, Tyr451, and Phe446 residues favorably contribute to the interactions between inhibitors and PP5. However, the Asp271 and Asp244 amino acid residues do not favor such interactions for some inhibitors. Through the QM calculations, we can suggest that the reactional energy of the coordination mechanism of these inhibitors in the PP5 active site is quite important and is responsible for the inhibitory activity. The AIM technique employed in this work was essential to get a better comprehension of the transition states acquired from the mechanism simulation. This work offers insights of how cantharidin-like inhibitors interact with human PP5, potentially allowing the design of more specific and even less cytotoxic drugs for cancer treatments. Graphical Abstract Interactions of cantharidin-like inhibitors with human protein phosphatase-5 in a Mg2+ system.
Keywords: racionální návrh léčiv; lidé; simulace molekulární dynamiky; proteinfosfatasy; Cations, Divalent; Drug Design; QM/MM; Humans; hořčík; Molecular dynamics; Serine/threonine phosphatase 5; Catalytic Domain; Cantharidin; jaderné proteiny; kationty dvojmocné; katalytická doména; Magnesium; AIM; Molecular Dynamics Simulation; Phosphoprotein Phosphatases; Enzyme Inhibitors; Cantharidin-like inhibitors; inhibitory enzymů; kantharidin; Nuclear Proteins